2018
DOI: 10.1038/s41598-018-24312-3
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of diabetes among migrants in the United Arab Emirates using a cross-sectional survey

Abstract: In 2011, the United Arab Emirates (UAE) had the 10th highest diabetes prevalence globally, but this was based on data that excluded migrants who comprise 80% of the population. This study assessed diabetes prevalence across the UAE population. A random sample of migrants was recruited from the visa renewal centers. Data were collected using interviews, anthropometric measurements and fasting blood for glucose, lipids and genetic analyses. 2724 adults completed the questionnaires and blood tests. Of these, 81% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 29 publications
3
44
0
Order By: Relevance
“…The UAEDIAB study had 5020 individuals across the UAE. 21,22 We selected the data from 4114 adult individuals that included simultaneous serum 25(OH)D level, lipid panels, and fasting serum insulin tests during 2013 for analysis ( Figure 1). These individuals met the following inclusion criteria: were 18 to 80 years of age and had simultaneous 25(OH)D, lipid panel, and fasting serum insulin tests inclusive.…”
Section: Study Populationmentioning
confidence: 99%
“…The UAEDIAB study had 5020 individuals across the UAE. 21,22 We selected the data from 4114 adult individuals that included simultaneous serum 25(OH)D level, lipid panels, and fasting serum insulin tests during 2013 for analysis ( Figure 1). These individuals met the following inclusion criteria: were 18 to 80 years of age and had simultaneous 25(OH)D, lipid panel, and fasting serum insulin tests inclusive.…”
Section: Study Populationmentioning
confidence: 99%
“…The United Arab Emirates National Diabetes and Lifestyle Study (UAEDIAB) study is a cross-sectional survey designed to investigate the prevalence of diabetes and associated risk factors in 827 Emiratis and 2724 expatriates living in Dubai, Sharjah, and the Northern Emirates [10][11][12]. UAEDIAB study has identified a list of patient's related measurements including obesity/BMI, hypertension, obstructive sleep apnea, and dyslipidemia that correlated with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 12,825 citations retrieved from the six databases, 48 research reports were found eligible (Fig. 1); 46 reported T2DM prevalence [45–90] while 24 reported pre-DM prevalence [48, 49, 51–57, 60, 62, 63, 66, 67, 70, 73, 75, 81, 85, 88–90].…”
Section: Resultsmentioning
confidence: 99%